Uncertainty Analysis and Calibration of Swat Model for Estimating Impacts of Conservation Methods on Streamflow and Sediment Yield in Thika River Catchment, Kenya - Gathagu, John Ng’ang’a; Mutua, Benedict M; Mourad, Khaldoon A; Oduor, Brian Omondi (International Journal of Hydrology Research, 2018)
Despite their imperative role in water resources management, distributed hydrological models like SWAT require calibration that can be challenging due to uncertainties of parameters involved. Prior to modelling of hydrological processes, these parameters and their uncertainty range need to be identified. The objective of this study was to conduct uncertainty analysis of hydrological processes and to calibrate the Soil and Water Assessment Tool (SWAT) for stream flow and sediment yield modelling in Thika River catchment. Sequential Uncertainty Fitting program (SUFI-2) was used to conduct sensitivity and uncertainty analysis. Stream flow was calibrated and validated between the years 1998 to 2013 for gauging stations 4CB05 and 4CB04. Manual sediments calibration was achieved by constraining the MUSLE parameters using the bathymetric survey data. Two uncertainty indices, p and r factor, were obtained as 0.72 and 0.65, 0.65 and 0.45 during calibration and validation, respectively. Statistical performance indicators showed a good match between the observed and simulated values which indicated that the model was well calibrated for simulation of stream flow and sediments yield in the catchment.